Maimendong and Qianjinweijing Tang (Jin formula) suppresses lung cancer by regulation of miR-149-3p. (10th August 2020) - Jiang, Zequn; Ma, Yanxia; Tian, Tian; Sun, Yan; Chen, Hao; Lu, Ye; Wu, Yan; Jiang, Haiying; Li, Wenting; Li, Li; Zhou, Hongguang; Wu, Mianhua
Abstract: Ethnopharmacological relevance: Maimendong and Qianjinweijing Tang (Jin formula), a classic Chinese formula, can enhance therapeutic efficacy and reduce adverse effects in patients with lung cancer. Aim of the study: To evaluate the anti-lung cancer effect of Jin formula in vivo and in vitro, and to explore the role of microRNA (miRNA) in the anti-lung cancer mechanism of Jin formula. Materials and methods: Cell survival was determined via a colorimetric method, and apoptotic condition was revealed by flow cytometric analysis. Cell migration and invasion were detected by scratch and transwell assays. Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) assay was applied to measure the changes of miRNA expression. Pathological histology of lung tissues were assessed by hematoxylin-eosin (HE) staining. Immunohistochemistry and immunoblotting were used to detect the expression of marker proteins of Wnt/β-catenin pathway. The relationship between miR-149-3p and MYC associated zinc finger protein (MAZ) was verified using a dual-luciferase reporter assay system. Results: Our findings demonstrated the anti-cancer effect of Jin formula in vitro, and revealed that Jin formula could suppress the proliferation, migration and invasion of human lung cancer A549 and H1299 cells. We also confirmed the capability of Jin formula to reduce tumor growth through the up-regulation of miR-149-3p and down-regulation of Wnt/β-catenin signaling in animal models. qRT-PCR analysis in vitro further confirmed a dose-dependent increase of miR-149-3p by treatment with Jin formula. Functional studies identified MAZ as a downstream target of miR-149-3p. Overexpression of miR-149-3p inhibited cell proliferation, migration, invasion and induced apoptosis in A549 and H1299 cells, similar to our findings on the effects of Jin formula treatment. In contrast, inhibiting the expression of miR-149-3p reversed the anti-cancer effects of Jin formula. Additionally, we revealed that miR-149-3p was involved in the anti-cancer effects of Jin formula, at least in part, by inhibiting MAZ expression and the Wnt/β-catenin signaling cascade. Conclusion: Our study illustrated that Jin formula suppressed the development of lung cancer and the mechanism may be associated with the miR-149-3p/MAZ/Wnt/β-catenin axis. Graphical abstract: Image 1 Highlights: Jin formula suppresses tumor growth in the mouse model of orthotopic Lewis lung cancer. Jin formula could suppress lung cancer cell proliferation, migration, and invasion in vitro. Jin formula suppresses lung cancer by up-regulation of miR-149-3p and down-regulation of Wnt/β-catenin signaling. MYC associated zinc finger protein (MAZ) is identified as a direct target of miR-149-3p.